Japanese Association for Marine Biology, JAMBIO - 一男 稲葉 (NIPPON SUISAN GAKKAISHI, 2021)
AIMS: Dermatophytes are a closely related group of fungi affecting approximately 25% of the global population. These pathogens are becoming increasingly resistant to antifungal agents, leading to recalcitrant infections. Therefore, there is an urgent need to identify new compounds with antifungal potential, particularly among those derived from plant sources. The present study aimed to evaluate the in vitro antifungal and antibiofilm activity of Lippia grata essential oil (LgEO) against eight dermatophyte clinical isolates. MATERIALS AND METHODS: LgEO was extracted, and chemically characterized by GC-MS. Antifungal activity was evaluated by determining the Minimum Inhibitory Concentration (MIC) and the Minimum Fungicidal Concentration (MFC), while antibiofilm activity was assessed using crystal violet staining and scanning electron microscopy (SEM). RESULTS: LgEO yield was 2.45%, while four major phytoconstituents were identified: carvacrol (46.56%), thymol (16.35%), p-cymene (13.52%), and γ-terpinene (7.75%). MIC values ranged from 48.82 µg ml-1 to 390.62 µg ml-1, and MFC values ranged from 48.82 µg ml-1 to 781.25 µg ml-1, demonstrating a fungicidal effect. All isolates were strong biofilm producers, and the percentage of biofilm inhibition by LgEO ranged from 29.94% to 89.52%. Microscopic analysis revealed morphological alterations in conidia, hyphae, and the exopolysaccharide matrix, including cell disruption, particularly during biofilm formation. CONCLUSION: Overall, LgEO demonstrated strong antifungal and antibiofilm activities, supporting further studies aimed at developing antiseptic products and topical antifungal drugs for the treatment of dermatophytoses.